Determination of Management Science: Ontology, Epistemology and Axiology Perspectives - Liana, Esti; Noermijati, Noermijati (International Journal of Advanced Multidisciplinary, 2024)
The purpose of this literature research onion study is expected to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of management science. The research article on the determination of management science: ontology, epistemology and axiology perspectives is a scientific literature article in the scope of management science. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or conduct a review of relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from academic online media such as the Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Ontology influences Management Science; 2) Epistemology influences Management Science; and 3) Axiology influences Management Science.